(untitled) - Couchman, Jason (New York, 2001)
Prepare to pass the OCP Introduction to Oracle9i SQL exam--a required exam for OCA/OCP DBA certification--using this Oracle Press study guide. You'll get complete coverage of all exam topics followed by practice questions and chapter summaries. The CD-ROM contains hundreds of practice exam questions in an adaptive format.
Keywords: Electronic data processing personnel,Database management,SQL (Computer program language),Xử lý dữ liệu nhân viên,Chương trình ngôn ngữ máy tính SQL,Quản lý cơ sở dữ liệu; Certification,Examinations,Chứng nhận,Sự nghiên cứu